EFFECT OF DIFFERENT LEVELS OF POTASSIUM ON GROWTH AND YIELD OF ONION VARIETIES (Allium cepa L.) AT CHITWAN, NEPAL - Pradeep bhandari; kalyani mishra tripathi; hom nath giri; bishal shrestha; nitya dahal (Fundamental and Applied Agriculture, 2025)
Crop nutrition is an essential part of production that affects growth, yield and quality of the crops. A field experiment was conducted in the farmer's field at Krishnapur, Chitwan, Nepal to study the effect of different levels of potassium on growth and yield of onion varieties during rabi season of 2019/2020. The experiment included two factors in two factorial randomized block design with total of 16 treatments replicated thrice. Four levels of potassium @ 0, 25, 50 and 75 kg ha-1 and four onion varieties namely Red Creole, Nasik-53, Dibya Gavran-11 and Fursungi were included in the experiment. Data on various growth and yield parameters were recorded. Application of 75 kg K ha-1 recorded maximum plant height (64.45 cm), maximum number of leaves (8.0) per plant and lowest number of days to harvesting (170.16 days) of bulbs. Similarly, application of 75 kg K ha-1 recorded maximum bulb length and maximum bulb diameter (3.77 cm and 4.21 cm), highest individual bulb weight (49.37 g) and highest marketable yield (24.14 mt ha-1). Results showed significant differences among varieties on majority of growth and yield parameters. Dibya Gavran-11 recorded maximum plant height (63.47 cm) while lowest number of days to harvesting of bulbs (168.83 days) was recorded in Fursungi. Similarly, Fursungi recorded maximum bulb length (3.79 cm), highest individual bulb weight (49.44 g) and highest marketable yield per hectare (24.23 mt ha-1). Field application of potassium @ 75 kg ha-1 depicted the best results with respect to growth and yield parameters of onion. Similarly, Fursungi responded and performed better than other three varieties. [Fundam Appl Agric 2025; 10(1.000): 303-310]